2004
DOI: 10.1021/jf0400765
|View full text |Cite
|
Sign up to set email alerts
|

Greek Plant Extracts Exhibit Selective Estrogen Receptor Modulator (SERM)-like Properties

Abstract: To prevent bone loss that occurs with increasing age, nutritional and pharmacological factors are needed. Traditional therapeutic agents (selective estrogen receptor modulators or SERMs, biphosphonates, calcitonin) may have serious side effects or contraindications. In an attempt to find food components potentially acting as SERMs, we submitted four plant aqueous extracts derived from Greek flora (Sideritis euboea, Sideritis clandestina, Marticaria chamomilla, and Pimpinella anisum) in a series of in vitro bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 32 publications
(37 reference statements)
0
52
0
5
Order By: Relevance
“…On the other hand, limited reports have shown that an aqueous extract from P. anisum demonstrated such biological effects as antioxidative, antimicrobial and selective estrogen receptor modulator-like activities. 17,18) However, it was uncertain which class of compounds contributed to those activities. We have shown in the present paper that the lignin-carbohydrate complexes from anise seemed to be the active principles for exhibiting antiviral and immunostimulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, limited reports have shown that an aqueous extract from P. anisum demonstrated such biological effects as antioxidative, antimicrobial and selective estrogen receptor modulator-like activities. 17,18) However, it was uncertain which class of compounds contributed to those activities. We have shown in the present paper that the lignin-carbohydrate complexes from anise seemed to be the active principles for exhibiting antiviral and immunostimulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both herbs increased the production of many hormones. Some studies showed that essential oil of both herbs is used for many purposes including milk production in female and relief dysmenorrhea, ease childbirth, increase sexual drive as well as treatment of menopause symptoms 42,43,44 . Shanoon A.K and Mahdi S J, 2012 were found that thyme has androgenic activity as it increased in ejaculate volume, sperm concentration, counts, movements and a significant decrease in motility and abnormality and significant increase in tests weight 45 .…”
Section: Discussionmentioning
confidence: 99%
“…at 100°C (Kassi et al, 2004), then 0.25 gm/Kg body weight (equivalent to 2.5 ml) of clear solution was given orally every day throughout the duration of the experiment to chamomile treated group (Abid et al, 2012).…”
Section: Extraction Of Chamomilementioning
confidence: 99%